POETICS OF LEITMOTIF IMAGES IN TARAS SHEVCHENKO’S EARLY CREATIVE WORKS - Пилип’юк, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article provides the analysis of text peculiarities of the orphan’s, fate’s, the sea’s image leitmotifs on the material of Shevchenko’s early poetry.